Схемное решение построения каскадного регистра сдвига - Kutsenko, G. V. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The shift register enables the sequential shifting of data while simultaneously tracking the shift time. The addition of extra gates and interconnections allows for an increase in bit width through cascading. The shift algorithm used reduces power consumption and improves noise immunity while maintaining high performance.